2014
DOI: 10.1177/0022219414522706
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Examination of the Persistence of Late Emerging Reading Disabilities

Abstract: There are some children who encounter unexpected reading difficulties in the fourth grade. This phenomenon has been described as late emerging reading disabilities (LERD). Using Grade 4 as a starting point, this study examined the reading development of 964 children between kindergarten and Grade 7. The results showed that 72.0% of children had typical reading performance in Grade 4, whereas there was 0.7% with poor word reading, 12.6% with poor reading comprehension, 2.5% with poor word reading and comprehens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 41 publications
5
47
1
3
Order By: Relevance
“…The customary assumption about the persistence of RD is contested by findings in recent studies on the stability of RD. These studies indicate that in addition to persistent RD cases, there are those with resolving RD (i.e., normal reading skills in later grades despite RD being identified during early grades) and those with late-emerging RD (i.e., RD identified during the later grades despite normal early reading skills) (e.g., Catts et al, 2012;Torppa et al, 2015;Etmanskie et al, 2016). These unstable groups are of particular interest because they may provide more understanding on the developmental risk and supportive mechanisms in RD.…”
Section: Introductionmentioning
confidence: 92%
“…The customary assumption about the persistence of RD is contested by findings in recent studies on the stability of RD. These studies indicate that in addition to persistent RD cases, there are those with resolving RD (i.e., normal reading skills in later grades despite RD being identified during early grades) and those with late-emerging RD (i.e., RD identified during the later grades despite normal early reading skills) (e.g., Catts et al, 2012;Torppa et al, 2015;Etmanskie et al, 2016). These unstable groups are of particular interest because they may provide more understanding on the developmental risk and supportive mechanisms in RD.…”
Section: Introductionmentioning
confidence: 92%
“…As this study focused on struggling readers, the study sample included all participating students who scored below the 25th percentile on the pretest of the standardized Gray Silent Reading Test (GSRT; Wiederholt & Blalock, ). We opted to use the 25th percentile because many research projects have used that cut‐off (e.g., Eason, Goldberg, Young, Geist, & Cutting, ; Etmanskie, Partanen, & Siegel, ; Fuchs et al, ; Rønberg & Petersen, ; Shapiro et al, ) or the 30th percentile (Wanzek et al, ) for identifying struggling readers to receive interventions. The GSRT was used to select students because it is a standardized reading test with sound psychometric properties.…”
Section: Methodsmentioning
confidence: 99%
“…Retelsdorf and Köller (2014) found reciprocal effects between spelling and reading comprehension in German students from grade 5 to grade 7. Other studies have shown that poor reading comprehension can be predicted by earlier spelling ability (Desimoni et al, 2012;Ritchey et al, 2015) and that children classified as poor comprehenders performed below typical readers on measures of spelling (Etmanskie, Partanen, & Siegel, 2016).…”
Section: Spelling and Reading Comprehension: Empirical Supportmentioning
confidence: 97%
“…Spelling data were available at only a single time point, so examination of longitudinal predictive relations was not possible. While evidence exists to suggest that spelling is predictive of reading comprehension over time (Chua et al, 2016;Etmanskie et al, 2016;Kim, Petscher, et al, 2013;Ritchey et al, 2015), other research has shown mixed results (Abbott et al, 2010;Desimoni et al, 2012). Furthermore, no studies have examined the longitudinal contribution of spelling while controlling for both word recognition and vocabulary.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%